The Concept of Suicide in Theravada Buddhism - Nuriani Nuriani; Junaidi Junaidi; Haudi Haudi; Kabri Kabri; Panir Selwen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the topic of suicide in the perspective of Theravada Buddhism using the literature review method. There are people holding the view of annihilation (vibhava-taṇhā) or craving for nonexistence, and they believe that suicide is the final solution to end the suffering. But The Buddha never taught to avoid suffering by committing suicide, and it will, for sure, not lead to liberation. Committing suicide will cause another chain of suffering and rebirth in the lower realm, even fall into endless cyclic existence (saṃsāra). That is why it goes “against the stream” of Buddhist moral teaching. The suicide was wrong because of the presence of desire or aversion accompanied by delusion (moha). The five precepts of the lay people (pañcasīla) and the pāṭimokkha of the monastic order, especially in the section of parajika, have clearly mentioned about the commitment to avoid killing. The idea of killing and suicide are inconsistent with the first precept of Pancasila and the Third precepts of patimokkha.  The concept of suicide is inconsistent with Buddhist ideas in the precepts for monks, nuns, and laypeople, that is why we have to understand hiri and otappa, so that we have strong life guidelines in carrying out our daily life processes.